2018
DOI: 10.1039/c8cp00124c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the co-loading and releasing of doxorubicin and paclitaxel using chitosan functionalized single-walled carbon nanotubes by molecular dynamics simulations

Abstract: Two widely used anticancer drugs, doxorubicin (DOX) and paclitaxel (PTX), possess distinct physical properties and chemotherapy specificity. In order to investigate their interaction mechanism with single-walled carbon nanotubes (SWCNTs), co-loading and releasing from the SWCNTs, all-atom molecular dynamics (MD) simulations were firstly carried out for different SWCNT systems, followed by binding free energy calculation with MM-PBSA. The results indicate that the co-loading of DOX and PTX onto the pristine SWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 41 publications
11
63
0
Order By: Relevance
“…Simulation results yielded a ∆G value of -21.64 kcal/mol that was near that of the reference study. These measurements can provide proof of this work and show consistency with previous works (38).…”
Section: Validation Testsupporting
confidence: 90%
See 2 more Smart Citations
“…Simulation results yielded a ∆G value of -21.64 kcal/mol that was near that of the reference study. These measurements can provide proof of this work and show consistency with previous works (38).…”
Section: Validation Testsupporting
confidence: 90%
“…To validate the computational procedure, a relevant recent article was chosen to reproduce a part of Gibbs free energy (∆G) calculation (38). This article has studied the co-delivery of DOX/PAX by a nanotube-chitosan carrier.…”
Section: Validation Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed pH-dependent drug release potential and anti-cancer activity of CNTs loaded with curcumin. Apart from curcumin, there is a range of studies demonstrating that anticancer herbal compounds can be effectively combined with CNTs: paclitaxel [80,81], docetaxel [82], vinca alkaloids [83], camptothecin [84,85], podophyllotoxin [86], quercetin [87], oridonin [88], etc.…”
Section: Carbon Nanotubes In Cancer Treatmentmentioning
confidence: 99%
“…The force field parameters for DOX and RHE molecules were obtained from the generalized Amber force field (GAFF). The atomic charges were generated with the restrained electrostatic potential (RESP) method [33,34]. An artificial box containing 8 DOX, 8 RHE and 2000 water molecules was generated by using the leap module in Amber Tools.…”
Section: Molecular Dynamics (Md)mentioning
confidence: 99%